Annual failure rates and marginal bone‐level changes of immediate compared to conventional loading of dental implants. A systematic review of the literature and meta‐analysis. Issue 6 (15th March 2014) - Engelhardt, Sebastian; Papacosta, Petros; Rathe, Florian; Özen, Jülide; Jansen, John A.; Junker, Rüdiger
Abstract: Background: Immediate loading of dental implants appears to be a successful option. Questions still remain whether annual failure rates (AFRs) as well as annual marginal bone‐level changes are comparable with conventionally loaded implants. Hypothesis: Immediately loaded implants (≤24 h after implantation) do not show different annual survival rates or peri‐implant bone‐level changes as compared to conventionally loaded implants (≥3 months after implantation). Material and methods: An electronic search in the National Library of Medicine and in Cochrane Central Register of Controlled Trials was performed for articles published up to November 2013. Only publications in English were considered. Additionally, the bibliographies of the full‐text papers were searched. Primary outcome variable was percentage AFR; secondary outcome variable was annual radiographic bone‐level change. Results: Electronic search yielded 154 full‐text articles; ten randomized controlled clinical trials were eventually meta‐analyzed. Annual failure rates were 2.3% and 3.4% for conventionally and immediately loaded implants, respectively. No difference in implant failure rates was found (RR: 0.82). Regarding marginal bone‐level changes, the weighted mean difference (WMD) between immediate and conventional loading amounted to 0.02 mm at 1 year ( P > 0.05), to 0.08 mm at 2 years ( P > 0.05), −0.10 mm at 3 years ( P > 0.05) and −0.3 mm at 5 years ( P < 0.05). The total WMD for the combined follow‐up was 0.01 mm ( P > 0.05). Conclusion: No clinically relevant differences regarding annual failure rates or radiographic bone‐level changes between conventionally and immediately loaded implants can be found for up to 5 years of follow‐up.